Designing CVT Slide Piece Molds for Cavity 24 Pieces on Injection Molding Machine - Latief, Alfan Ekajati; S., M. Pramuda Nugraha; S., Adimas Prasetyo; Prianto, Ramdan; Sarmada, Sarmada; Irfan, Laode Mochamad (METAL: Jurnal Sistem Mekanik dan Termal, 2024)
Composite materials are often used in the industrial world, one of which is in the automotive industry. Material composite based on polypropylene high impact (PPHI) and natural fiber can be used to create slide piece components on the CVT of automatic motor vehicles. In this study, we will design molds from injection molding on an industrial scale en masse, producing a slide piece product made from composite materials. This research is a development of the previous injection molding mold. In the study, the solidworks software will compare three types of multi-cavity, namely circular, series, and parallel, to get more efficient and effective molds. This multi-cavity type is designed to print PPHI material and pineapple fiber with a volume fraction of 20% and a mesh of 170. The mold material designed is made of stainless steel 2316 for cavity and core parts with a size of 180mm x180mm. Using simulation plastic on solidworks, the simulation results obtained a type of circular type that can be applied to injection machine molds because it has the most effective pressure value of 4.8 MPa and its geometric shape. Then obtained a fill time of 1,89s and volumetric shrinkage at the end of fill at a max of 17.56%, which is more efficient.